Cell population dynamics in the course of adult hippocampal neurogenesis: Remaining unknowns. Issue 4 (18th October 2022) - Olpe, Cora; Jessberger, Sebastian
Abstract: Neural stem cells (NSCs) generate new neurons throughout life in the mammalian hippocampus. The distinct developmental steps in the course of adult neurogenesis, including NSC activation, expansion, and neuronal integration, are increasingly well characterized down to the molecular level. However, substantial gaps remain in our knowledge about regulators and mechanisms involved in this biological process. This review highlights three long‐standing unknowns. First, we discuss potency and identity of NSCs and the quest for a unifying model of short‐ and long‐term self‐renewal dynamics. Next, we examine cell death, specifically focusing on the early demise of newborn cells. Then, we outline the current knowledge on cell integration dynamics, discussing which (if any) neurons are replaced by newly added neurons in the hippocampal circuits. For each of these unknowns, we summarize the trajectory of studies leading to the current state of knowledge. Finally, we offer suggestions on how to fill the remaining gaps by taking advantage of novel technology to reveal currently hidden secrets in the course of adult hippocampal neurogenesis.